IMPLEMENTASI IMPLEMENTASI SISTEM PERADILAN ELEKTRONIK DALAM PENYELESAIAN PERKARA (Studi Kasus Pengadilan Negeri Watampone Kelas 1A) - Ulfa, Ulfa; Darliana (Journal of Law and Administrative Science, 2025)
This study aims to determine the implementation of the electronic justice system using e-Court and e-Berpadu in the Watampone District Court Class 1A and identify the obstacles and efforts made by the Watampone District Court Class 1A in implementing electronic justice. This type of research is a normative-empirical or normative-applied legal research. This research is a qualitative research. This study obtained data through observation and interviews with sources and respondents who use the electronic justice system in the Watampone District Court Class 1A. The results of the study indicate that the implementation of the electronic justice system in the Watampone District Court Class 1A has been running in accordance with the provisions of the Supreme Court in the use of E-Court and E-Berpadu which have been utilized to support the electronic justice process in terms of administration and at the trial stage. However, the implementation of this system still faces several obstacles, including users who do not understand the electronic justice system and disruptions to infrastructure such as networks and systems. The solutions implemented include providing assistance to service users who have difficulty operating the electronic justice system, namely e-Court and e-Berpadu, as well as providing an IT department at the Watampone District Court to handle any system damage to the e-Court and e-Berpadu electronic justice systems.